Conceptualization of Jurimetry on the Determination of Women's Rights After Divorce - Putri, Rizky Silvia (Golden Ratio of Data in Summary, 2025)
Divorce in Indonesia in 2020-2022 has always increased in number. Related to divorce, Islamic law, since its inception, has raised many values of humanity and justice, especially towards women, so that it regulates in such a way that divorce does not give rise to injustice, especially towards women. Women's rights after divorce have been regulated in several laws and regulations. The embodiment of these regulations is then stated by the judges in their decisions. Even though it has been regulated in such a way, there are still problems in resolving disputes over women's rights after divorce, namely, regarding the method used by judges in determining the amount of women's rights after divorce. So it is important to examine a theory that can provide certainty and accuracy in determining the amount of women's rights after divorce. The theory in question is jurimetry. The problems in this study are first, what are the rights of women after divorce? Second, what is the concept of jurimetry in determining women's rights after divorce? This type of research is library research or a literature study. Women's rights after divorce include iddah, mut'ah, and past livelihoods. The study of the use of jurimetry using variables based on legal norms makes this method fulfill the concept of distributive justice and also procedural justice. Distributive justice is fulfilled because, in imposing post-divorce obligations, the judge also looks at the role and services of each party in the household, whether during the marriage, each husband or wife has carried out their obligations, so that when a divorce occurs, each party can obtain their rights. As for the fulfillment of procedural justice because the judge, in formulating a decision based on jurisprudence, in addition to having to apply the correct procedural procedures, also provides clear legal considerations based on statutory regulations.